CXCL5/CXCR2 axis in tumor microenvironment as potential diagnostic biomarker and therapeutic target. Issue 2 (31st March 2020) - Zhang, Wen; Wang, Huishan; Sun, Mingyang; Deng, Xueting; Wu, Xueru; Ma, Yilan; Li, Mengjing; Shuoa, Said Maisam; You, Qiang; Miao, Lin
Abstract: The components of the tumor microenvironment (TME) in solid tumors, especially chemokines, are currently attracting much attention from scientists. C‐X‐C motif chemokine ligand 5 (CXCL5) is one of the important chemokines in TME. Overexpression of CXCL5 is closely related to the survival time, recurrence and metastasis of cancer patients. In TME, CXCL5 binds to its receptors, such as C‐X‐C motif chemokine receptor 2 (CXCR2), to participate in the recruitment of immune cells and promote angiogenesis, tumor growth, and metastasis. The CXCL5/CXCR2 axis can act as a bridge between tumor cells and host cells in TME. Blocking the transmission of CXCL5/CXCR2 signals can increase the sensitivity and effectiveness of immunotherapy and slow down tumor progression. CXCL5 and CXCR2 are also regarded as biomarkers for predicting prognosis and molecular targets for customizing the treatment. In this review, we summarized the current literature regarding the biological functions and clinical significance of CXCL5/CXCR2 axis in TME. The possibility to use CXCL5 and CXCR2 as potential prognostic biomarkers and therapeutic targets in cancer is also discussed